Efficacy of landmark based blind transverse abdominis plane block for post-operative pain relief in inguinal hernia - Purohit, Swetha; Kavi, Chandrashekarappa; Halli, Sudharani (Asian Journal of Medical Sciences, 2023)
Background: Pain after open hernia surgery can be moderate-to-severe and is known to be associated with prolonged hospital stay and delayed return to normal daily activities. Aims and Objectives: We aimed to investigate the effect of a blind landmark-based approach of transversus abdominis plane (TAP) block on patients undergoing elective inguinal hernia repair surgery under spinal anesthesia. Materials and Methods: This was a prospective, randomized, controlled, and clinical trial consisting of 60 patients scheduled for inguinal hernia repair under spinal anesthesia. Patients in Group-1 received TAP block by landmark based blind technique, whereas those in Group-2 did not receive TAP block. Pain assessments were scored for all patients at rest and movement at 2, 4, 6, 12, and 24 h after surgery using visual analog scale. Results: The pain scores in the post-operative period, during rest and movement, were significantly lower in patients that received TAP block. Significant number of cases reported nausea and vomiting or headache in Group-2 due to increase requirement of analgesics for pain relief during first the 24 h of post-operative period. Conclusion: Landmark-based blind TAP block may be an effective way of providing analgesia in patients undergoing elective open inguinal hernia repair under spinal anesthesia.